Uplink performance evaluation of broadband systems which adopt a massive MU-MIMO approach - Torres, Paulo (2018)
This paper deals with an Orthogonal Frequency Division Multiplexing (OFDM)-based uplink within a Multi User (MU)-Multi-Input Multi-Output (MIMO) system where a ”massive MIMO” approach” is adopted. In this context, either an optimum Minimum Mean-Squared Error (MMSE) linear detection or a reduced-complexity Matched Filter (MF) linear detection are considered. Regarding performance evaluation by simulation, several semi-analytical methods are proposed: one performance evaluation method in the optimum (MMSE) case; two performance evaluation methods in the MF case. This paper includes performance results for uncoded 4-Quadrature Amplitude Modulation (QAM)/OFDM transmission and a MUMIMO channel with uncorrelated Rayleigh fading, under the assumptions of perfect power control and perfect channel estimation. The accuracy of performance results obtained through the semi-analytical simulation methods is assessed by means of parallel conventional Monte Carlo simulations [10]. The performance resultsare discussed indetail andwe also emphasize the achievable ”massive MIMO” effects, even for the reducedcomplexity detection techniques, provided that the number of BS antennas is much higher than the number of antennas which are jointly employed in the terminals of the multiple autonomous users.